Son Thang : - Solis, Gary D. (Bantam books, 1997)
In this engrossing true courtroom drama, Gary D. Solis, a former Marine combat officer who teaches law at the U.S. Military Academy at West Point, draws on his considerable experience to describe the Marine Corps' worst known war crime in Vietnam. Although overshadowed by the infamous My Lai massacre, the murder of sixteen women and children by five Marines at Son Thang-4 raised serious questions for the Corps and the Uniform Code of Military Justice. Were the five Marines of the self-styled killer team sent to Son Thang-4 on 19 February 1970 carrying out orders to punish the hamlet or reacting to snipers when they opened fire on noncombatant civilians at point-blank range? Were their actions simply a consequence of weeks of unrelenting combat in which fellow Marines were killed by the invisible Viet Cong and their boobytraps? Using trial records and extensive interviews, Solis brings to life the host of military and civilian attorneys, judges, and juries who wrestled with these and other thorny questions in the midst of a combat zone. Here for the first time is the full story of what happened at Son Thang-4, including the controversial deliberations and verdicts--a study as pertinent today as it was more than twenty-five years ago.